Direct Method: Concept, Characteristics, and Steps for Implementation in Arabic Language Learning - Afriati, Intan; Rizki, Gebrina; Humaira, Siti; Hidayat, Rahmat (MANDAILING GLOBAL EDUKASIA, 2025)
This study discusses the application of the direct method (mubasyarah) in learning Arabic. This method emphasizes the full use of Arabic without the involvement of the mother tongue. This method aims to form students' active communication skills in Arabic in a practical and functional manner. Its main characteristics include direct interaction, contextual learning, and inductive grammar teaching. The advantages of this method include high motivation of students, intensive pronunciation exercises, and the use of visual media to clarify meaning. Meanwhile, the disadvantage lies in the limited use in large classrooms and the dependence on high teacher competence.